How Knowledge Transfer Mechanism and Integrity Improve Local Government Performance: Evidence from Indonesian Regional Agencies - I Gusti Ayu Ngurah Lita Rumiati; Putu Kepramareni; Gde Bayu Surya Parwita (International Journal of Economics, Management and Accounting, 2026)
This study was motivated by the importance of improving the performance of regional government agencies in supporting the implementation of the Government Agency Performance Accountability System (SAKIP) to achieve effective, professional, transparent, and accountable governance. Despite increasing attention to public sector accountability, empirical evidence explaining how competence mediates the relationship between knowledge transfer mechanisms, integrity, and organizational performance remains limited, particularly in Indonesian local governments. The study aimed to analyze the effects of knowledge transfer mechanisms and integrity on the performance of regional government agencies through competence in the Regional Government of Badung Regency. This study employed a quantitative approach using a survey method. The population consisted of 37 regional government agencies within the Regional Government of Badung Regency. The sample was determined using purposive sampling, consisting of employees who were members of the SAKIP Team in each regional government agency. Data were collected through questionnaire distribution and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS), to test direct and indirect relationships between variables. The results showed that the knowledge transfer mechanism had a negative but insignificant effect on the performance of regional government agencies. Integrity had a positive and significant effect on the performance of regional government agencies. Both the knowledge transfer mechanism and integrity had positive and significant effects on competence. Competence also had a positive and significant effect on the performance of regional government agencies and mediated the effects of the knowledge transfer mechanism and integrity on organizational performance. Based on the research results, it can be concluded that improving regional apparatus performance is influenced by the integrity and competence of the apparatus, while the knowledge transfer mechanism contributes to performance improvement through competence as a mediating variable. Therefore, the Badung Regency Government is advised to strengthen the integrity of the apparatus through continuous guidance and supervision and improve the competence of the apparatus through education, training, and capacity building to support the realization of professional and accountable governance.